Czytanie (z) roślin. Obraz i słowo w twórczości Urszuli Zajączkowskiej - Lekowska, Daria (Studia Europaea Gnesnensia, 2018)
The aim of this paper in to show the work of Urszula Zajączkowska in the light of eco-posthuman notions. The analysis will focus on film and poetry which, according to the Warsaw botanist, become complementary tools of the scientific narrative, and serve to describe relationships between humans and other organisms.